Maurice du Plessys, a French Poet Friend of Rubén Darío - Schmigalle, Günther (Anales de Literatura Hispanoamericana, 2010)
The influence that the French writers exercised on Rubén Darío’s work has been widely studied by the critique. Nevertheless, the studies have stayed in a background on the relations that the Nicaraguan poet established with some intellectual Frenchmen. In this article there is analyzed the influence that Maurice du Plessys could exercise on Darío across the correspondence that both supported.